Toppling Things as Memorial Contestation : Spectacle and Affect of Monument Removal - El-Mecky, Nausikaä; Macsotay, Tomas (Literature and Cultural Studies E-Books Online, Collection 2025., 2025)
Following the murder of George Floyd in 2020, monuments became a focal point: protestors toppled or spray-painted them, even danced on them. These politically, visually, and emotionally potent events may have looked instantaneous, yet frequently sprang from years of activism, as well as protracted political and academic debate. Toppling Things challenges stereotypical notions monument topplings as riotous, spontaneous, or irrational. Bringing together the ideas and emotions, the uncertainty and convictions, of artists, activists, and academics, the volume rejects a neatly tied-up, distant narrative. As it sheds light on the global, personal, immediate, and historical processes around the fall of a monument, the volume engages directly with the complexity of toppling activism and monument removal as a form of lived experience.